The Formation of Responsible Subjects Through Narrative-Based Entertainment Products: The Case of the Podcast "Zeit Verbrechen" - Riehle, Ramona; Kogler, Stephanie (Advances in consumer research, 2023)
Riehle and Kogler examine the impact of true crime podcasts on consumer behavior and societal engagement. True crime podcasts offer a unique blend of entertainment and education. Consumers are drawn to the non-fictional nature of these narratives, which provide a glimpse into real-life crimes and injustices. The critical approach of many true crime podcasts differentiates them from sensationalist true crime media. True crime podcasts can empower consumers to become more critical thinkers and active citizens. By understanding the complexities of crime and justice, consumers can develop a stronger sense of social responsibility. These narratives can motivate consumers to take action to prevent crime and support victims.